Study of Disease Profile of Patients Admitted in Cardiac Unit in a District Hospital of Bangladesh (Bangladesh Heart Journal, 2022)
Objectives: Aim of our study was to predict the pattern of disease of patients admitted in cardiac unit in a district hospital of Bangladesh. Material and Methods: This observational study was conducted in the department of cardiology, General hospital, Sirajgonj, Bangladesh during the period of 02 months from June to July, 2019. Total of 504 patients were enrolled who were admitted in cardiac unit in Sirajgonj 250 bed General Hospital during two months’ period from 1st June to 31st July, 2019. Every admitted patient was included in the study and history, clinical examination and investigation was done. Risk factors and complications ware noted. After diagnosis, treatment was given and outcome was recorded. Result: Age ranges was 23 to 74 year mean age was 55.9±13.6, 322 were male and 182 were female. According to risk factors, 211 were smoker, 206 were hypertensive, 166 have dyslipidemia, 110 have diabetes mellitus, 146 were prediabetic, 70 have family history of IHD and 20 were obese. The patients were diagnosed as AMI (ST elevation)-115, NSTEMI-45, UA-40, CSA-100, CCF-20, HTN- 50, MS-7, MR-5, AS-5, RMI-15, OMI-20, ICM-13, ASD-3, VSD- 5, TOF-2, PPCI-2. Admitted patients have following complications- LVF-50, PE-2, PVC-55, AF-30, Cardiogenic shock-20, SVT-15, VT-10, CHB-10, VF-5 and atrial flutter-5. Comorbidity profile were COPD-36, Bronchial Asthma- 40, CKD-30, Musculoskeletal pain-20, AN-15, PUD-10, RTI- 10, CVD-76, Tubercular pleural effusion-10, Anaemia-15, Cervical spndylosis-5, UTI-5, RA-5, Sacroilitis-5. Following were the treatment outcome cured-40, improved-414, referred-35 and death-15. Conclusion: Most of the patients were male and smoking was the predominant risk factor. Acute STelevation MI was the predominant primary disease. PVC was the most common complication and CVD was the highest comorbidity. Death was 2.9% and it was most commonly due to Acute ST elevation MI with development of LVF with cardiogenic shock.Bangladesh Heart Journal 2022; 37(1): 10-15